Partners in suspense : Critical essays on Bernard Herrmann and Alfred Hitchcock - Donnelly, K. J. (Kevin J.); Rawle, Steven (Book collections on Project MUSE., 2017)
This volume of essays explores the tense relationship between Alfred Hitchcock and Bernard Herrmann, featuring new perspectives on their collaboration. Featuring essays by leading scholars of Hitchcock's work, including Richard Allen, Charles Barr, Murray Pomerance, Sidney Gottlieb and Jack Sullivan, the collection examines the working relationship between the pair and the contribution that Herrmann's work brings to Hitchcock's idiom. Examining key works, including The Man Who Knew Too Much, Psycho, Marnie and Vertigo, the essays explore approaches to sound, music, collaborative authorship and the distinctive contribution that Herrmann's work with Hitchcock brought to this body of films, examining the significance, meanings, histories and enduring legacies of one of film history's most important partnerships. By engaging with the collaborative work of Hitchcock and Herrmann, the book explores the ways in which film directors and composers collaborate, how this collaboration is experienced in the film text, and the ways in which such partnerships inspire later work.--Publisher description.